PENGARUH MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA PADA PEMEBELAJARAN TEMATIK KELAS V DI SEKOLAH DASAR - Raya Sigalingging; Darinda Sofia Tanjung; Rumiris Lumban Gaol (Universitas Negeri Medan, 2021)
This study is a quantitative study that aims to determine the effect of the Quantum Teaching learning model on student learning outcomes conducted at SD Negeri 106144 Sei Mencharim 2020/2021. This research method is descriptive method. The population of this study were all fifth grade students of SD Negeri 106144 Sei Menistrim which consisted of one class with a total of 30 students. The results showed that the Quantum Teaching model was included in the good category with an average of 80.7, the correlation coefficient was 0.705, which means that r_count (0.705) r_table (0.361), then h_a is accepted. Hypothesis testing shows that tcount > ttable is 6.363 1.697, thus stating that h_a is accepted. It can be concluded that the Quantum Teaching learning model has an influence on learning outcomesKeywords: Learning Outcomes, Thematic, Quantum Teaching Model